Estudio de prefactibilidad para la instalación de una planta de producción de bebida rehidratante a base de quinua - Llacsahuanga Ramos, Javier Alejandro (2019)
One of the main problems of athletes and people who practice sports for passion is dehydration, this happens because the human body to avoid overheating its structure generates sweat that cools the body and is the sweat where they are lost the mineral sales vital for our body. The human body generates a feeling of fatigue (fatigue) due to dehydration, with the consequence that people can not perform as much as possible and that they are prone to muscle injuries due to the loss of mineral salts such as sodium and potassium that serve a correct absorption of water in our body. Due to these reasons and that according to Euromonitor (2015); the isotonic beverage market is growing every year, it is proposed to study the realization of a project for the manufacture of a drink of this type that contains natural protein and that does not require further refinements, or processes for its preparation.